Evaluation of Physical Characteristic in Ciprofloxacin Tablet Dosage Form and Quantitative Analysis by UV- Spectrophotometry and HPLC - Najim, Nigar A.; Jalal, Renas R.; Qadr, Nigar M.; Sabeer, Sakar B. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Ciprofloxacin is used as an active ingredient in different dosage forms, including tablet, which is used for treatment of various infectious diseases. Quantitative determination was performed by UV/Visible spectrophotometer and high performance liquid chromatography. Evaluation of the physicochemical property of Ciprofloxacin was performed by various methods: weight uniformity test, friability, hardness, thickness, diameter, disintegration, dissolution test loss on drying and Karl Fischer titration. The results have shown that the percentages of the assay witch determined by UV/Visible spectrophotometry and HPLC are complying with United State Pharmacopeia. The results for weight variations, diameter, thickness, hardness, friability, water content, disintegration and dissolution are within the normal range. In addition, there is no significant difference between core and coated tablets. Ciproneer tablets (Ciprofloxacin, Pioneer, Iraq) of this batch can be marketed and prescribed for the patient because it is safe and effective.
Keywords: Ciprofloxacin; Quantitative; Physical Characteristic; UVSpectrophotometry; HPLC